2015
DOI: 10.1016/j.aller.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Fraction of exhaled nitric oxide in healthy Chilean schoolchildren aged 8–15 years

Abstract: This study suggests that FENO values higher than 27ppb are likely to be abnormal and would reflect airway inflammation in children as those in the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
1
4
1
1
Order By: Relevance
“…This pattern was observed both for year 3 BMI% and time-varying BMI%. Previous studies have found no association between F ENO 50 in children and weight [6][7][8], body surface area [8] or BMI [7,10,29], with exception of a reported negative association with BMI z-score, primarily in atopic children [30] and weak positive correlation for body surface area [7]. BMI%, which is considered in the present study, may better represent being under-/overweight at a given age and sex.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…This pattern was observed both for year 3 BMI% and time-varying BMI%. Previous studies have found no association between F ENO 50 in children and weight [6][7][8], body surface area [8] or BMI [7,10,29], with exception of a reported negative association with BMI z-score, primarily in atopic children [30] and weak positive correlation for body surface area [7]. BMI%, which is considered in the present study, may better represent being under-/overweight at a given age and sex.…”
Section: Discussioncontrasting
confidence: 68%
“…Prior studies of the distribution and determinants of F ENO 50 in healthy paediatric populations were based on single cross-sectional measurements among children across a range of ages [5][6][7][8][9][10][11], which may have missed important patterns in F ENO 50 change as children grow. Serial measurements within the same set of children as they age are likely to be more informative for understanding trajectory of F ENO 50 across childhood and adolescence as well as potential determinants of this evolution.…”
Section: Introductionmentioning
confidence: 99%
“…NO formation is already detected at birth [ 22 , 23 ] and is important in humans, which are under strict biological control. NO formation is a complex and energy consuming process whereby NO is produced by inducible NO synthase in the airway epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…However, reports on the relationship between FeNO levels and age compared subjects aged 35–44 years to those aged 64 years and older [18], or between subjects aged less than 60 years to those aged 60 years and older [19]: that is, each group covered a wide age range. Reports on children include a study finding no difference in FeNO level by age in children aged 5–16 years [20], and a study that demonstrated no correlation between FeNO level and age in a group of children aged 8–15 years [21], suggesting that it was highly unlikely that the 1-year difference in age was responsible for the difference in FeNO levels.…”
Section: Discussionmentioning
confidence: 99%